The Political and Economic Impacts of Rohingya Refugee Crisis: Challenges and Opportunities of Humanitarian Intervention in Post-Conflict Space - Satria Rizaldi Alchatib (Insignia: Journal of International Relations, 2021)
The crisis of Rohingya refugee has been agitating bilateral relations among South East Asian and South Asian countries particularly Bangladesh. Beside the massive influxes of ingoing refugees, the crisis contributes to a massive economic decline in addition to poor assistantship of their host countries. Building from these, this article aims at examining the local community integration policy jointly delivered by the United Nations High Commissioner for Refugee (UNHCR) and International Organization for Migration (IOM) together with the governments of host countries in promoting cultural reunification between refugees and native population of Bangladesh, Malaysia, Indonesia and Thailand. Moreover, this article seeks to explore the way refugee navigates destination based on sociological, anthropological, and geographical resemblance in which encompasses religious, ethnical, historical, and economic considerations. Methodologically, this article is deliberated through a mix qualitative method where discourse and content analysis are being employed respectively. As a result, this article signifies the inherent legitimacy of cultural and religious institutions that breaches the pre-existing legal restraint as well as weighing up its supremacy against the government’s interest and political agenda. Eventually, the ultimate outcome of this research draws the process on how refugees and native inhabitants shapes reciprocal relationship in times of international rejection and how they influence the development of destination countries economically and politically. Keywords: Bangladesh, community integration, humanitarian intervention, Indonesia, Rohingya refugee